Trends in Tobacco Consumption - a Comparative Analysis of WHO European Region Countries - Adam Mateusz Suchecki (Comparative Economic Research. Central and Eastern Europe, 2020)
Tobacco consumption, as well as the consumption of any other psychoactive substances, lead to addictions, which is a serious problem that modern societies have to face. To reduce the negative consequences of nicotine consumption and to provide sustainable development, many governments, in both developed as well as developing countries, adopt policies to reduce tobacco production and consumption. For example, they implement various health programs to combat addiction, and they also provide appropriate financial and fiscal resolutions. Any actions taken at different decision-making levels are often bounded with economic and financial policies of a particular state, including fiscal policy. State interventionism concerning tobacco is most visible in developed countries such as the US, Canada, and European Union countries. Developing countries and Asian countries have also started to introduce regulations concerning tobacco consumption on a large scale in response to the negative effects of nicotinism. The main aim of the paper is to show consumption trends as well as the fiscal and price policies of tobacco products. The theoretical part is supplemented by data from reports and analyses presented by the World Health Organization (WHO).
Keywords: H71; I18; 330; Tobacco; Tax; public policy